Impact of apps aesthetics on revisit intentions of food delivery apps: The mediating role of pleasure and arousal. (November 2021) - Kumar, Sushant; Jain, Aarushi; Hsieh, Jung-Kuei
Abstract: Online food delivery (OFD) apps are changing the way we consume food. Despite increasing the popularity of OFD apps, limited studies have explored the reason behind popularity which contributes to the revisit intentions. This study investigates the drivers of revisit intentions by adopting stimulus-organism-response (SOR) theory and pleasure arousal dominance (PAD) theory as a theoretical lens. A model is conceptualized by including aesthetic formality and aesthetic appeal of OFD apps as stimuli, pleasure, and arousal as the internal state of the organism, and revisit intentions and word of mouth (WOM) as a response. Data is collected from OFD app users through a survey questionnaire. Findings indicate that aesthetic appeal is associated with pleasure and arousal. Aesthetic formality is associated with pleasure, word of mouth, and revisit intentions. Further, pleasure influences arousal, word of mouth, and revisit intention. The findings also confirmed the mediating role of pleasure and arousal. The study contributes to the practice and theory in the context of online food delivery apps. Highlights: The study adopts SOR and PAD theory in the context of online food delivery (OFD) apps Aesthetic appeal is associated with pleasure and arousal Aesthetic formality influences pleasure, word of mouth, and revisit intentions Pleasure is associated with arousal, word of mouth, and revisit intentions The mediating role of pleasure and arousal is also confirmed